Effects of letrozole co-treatment on the cumulative live-birth rate among normal responders in gonadotropin-releasing hormone antagonist cycles - Zhang, Shuyi; Gao, Fumei; Fu, Min; Shen, Huan; Wang, Yanbin; Han, Hongjing (Frontiers in Medicine, 2022)
Studies have shown that letrozole cotreatment can improve clinical outcomes in high and poor responders in GnRH-antagonist protocol. However, whether letrozole is also beneficial to normal responders is not known. To investigate the clinical value of letrozole cotreatment during ovarian stimulation in vitro fertilization for normal ovarian reserve patients who were treated with the GnRH antagonist protocol, we conducted a retrospective study that based data from 1 January to 31 December 2017 for all IVF–ICSI GnRH-antagonist protocols. A total of 252 women who aged <40 years, FSH＜10 IU/L on day 3 and antral follicle counting (AFC)＞6 were included in the analysis (96 in the letrozole group and 156 in the no-letrozole group). The cumulative live-birth rate was calculated as the first live birth achieved after all cycles having an embryo transfer (cycles using fresh embryos and frozen–thawed embryos) among both groups. The initial gonadotropin (Gn) dosage and total Gn dosage were significantly lower and the number of days of Gn treatment was significantly fewer in the letrozole group than the non-letrozole group (p < 0.05). There were also significant between-group differences in luteinizing hormone, estradiol, and progesterone concentrations; and the number of metaphase II oocytes on the day of human chorionic gonadotropin treatment (p < 0.05). There was a significant difference in the implantation rate between the two groups that the letrozole group higher than the non-letrozole group (39.79% vs. 27.96%, p = 0.006), but there was no significant difference in the cumulative live-birth rate. The combination of letrozole with a GnRH antagonist may have no effect on the clinical pregnancy rate or cumulative live-birth rate in patients with a normal ovarian reserve. However, letrozole may increase the rate of embryo implantation and may reduce the requirement for exogenous gonadotrophins and, consequently, the cost of an IVF treatment cycle.